Investigation on minute holes of woven fabrics for wide-band micro-perforated sound absorbers - Prasetiyo, Iwan; Gunawan; Yuliarto, Brian; Putra, Azma; Irianto (MDPI, 2023)
Woven fabric perforation is helpful to be adopted to meet the microstructure requirement of a micro-perforated panel (MPP) absorber. Unlike conventional MPP, the woven fabric micro-perforations are formed by yarn in the x (weft) and y (warp)-directions. Hence, minute holes of the MPP with a diameter of 0.1–0.3 mm or a high perforation ratio are expected to be easily fabricated, while such a specification is difficult to realize on a solid surface, as found in some studies. The study presented here focuses on the use of minute holes in MPP absorbers by woven fabrics and discusses the minute hole properties of woven fabrics and their associated absorption characteristics. Theoretical results by Maa’s model are also used to validate resulting characteristics found from the experimental investigations. It is found that minute holes with around 0.10–0.20 mm diameter have been successfully fabricated by controlling weft yarn density. The woven fabrics are capable of producing half-absorption bandwidth of up to 5000 Hz (>3 octaves), while the peak of the absorption coefficient can be more than 0.8. In addition, varying hole diameter with the order of 10−2 mm can change the absorption behavior for both peak absorption and absorption bandwidth. Such behavior is confirmed by comparing the results with the theoretical model. This study also indicates that Maa’s model is still applicable for predicting absorption of MPP developed based on woven fabric material.